Chronic Medical Conditions in Croatian War Veterans Compared to the General Population: 25 Years after the War - Dario Nakić; Mira Stipčević; Martina Morić Perić; Zoran Bakotić; Jelena Vučak Lončar; Kristina Bačkov; Marina Vojković; Jelena Jakab; Aleksandar Včev (Acta Clinica Croatica, 2023)
Many published reports have documented an increased prevalence of chronic medical conditions among veterans, but there were only a few studies that compared these increases with the general population. The aim of this study was to determine differences in chronic medical conditions between Croatian war veterans and the general population. This study included two groups of subjects, i.e. 1453 participants who are Croatian war veterans and 1429 participants from the general population. Medical history, physical examination, laboratory tests and specific diagnostic procedures were taken during systematic physical examination in both groups. The prevalence of hypertension, diabetes, hyperlipidemia, hypothyroidism and hyperthyroidism, chronic obstructive pulmonary disease, coronary heart disease, malignancy, psychiatric diseases, cholelithiasis, nephrolithiasis, smoking and alcohol consumption was analyzed. Croatian war veterans were found to be more likely to develop hypertension than individuals in the general population (29.5% vs. 24.3%), as well as diabetes (7.3% vs. 3.8%), hyperlipidemia (56.4% vs. 27.3%), hyperthyroidism (3.1% vs. 0.8%), coronary heart disease (4.3% vs. 1 %), malignancy (4.1% vs. 2.2%), psychiatric diseases (15.4% vs. 1.1%), and alcohol consumption (53% vs. 29%). Significant difference was found in favor of the general population for hypothyroidism (14.3% vs. 8%). There were no differences in the prevalence of chronic obstructive pulmonary disease, cholelithiasis, nephrolithiasis, and smoking. Our findings confirmed the hypothesis of a higher prevalence of cardiovascular diseases, malignancy and psychiatric diseases among Croatian war veterans and emphasized the need of better control of their medical conditions.